Biopharmaceutical and antifungal properties of ellagic acid-cyclodextrin using an in vitro model of invasive candidiasis - Gontijo, Aline V. L. [UNESP]; G Sampaio, Aline Da [UNESP]; Koga-Ito, Cristiane Y [UNESP]; Salvador, Marcos J (Taylor & Francis, 2019)
Aim: To investigate biopharmaceutical and antifungal properties of pure and complexed ellagic acid. Materials & methods: Caco-2 cells cultured in a Transwell® inserts were infected with Candida albicans to develop an in vitro model. Ellagic acid was complexed with cyclodextrins. Microbial compositions, ellagic acid concentration as function of time and characterization studies of complexes were evaluated. Results: Ellagic acid presented ability to reduce C. albicans invasion, although this was not statistically significant. Its poor water solubility and absorption probably limited this ability. Water solubility was increased after complexation with hydroxypropyl-β-CD; however, ellagic acid/hydroxypropyl-β-CD did not improve the antifungal activity. Conclusion: Although ellagic acid presented a promising antifungal activity, its biopharmaceutical properties limit such activity and should be improved.
Keywords: Candida albicans; cyclodextrin; ellagic acid; in vitro model of invasive candidiasis